ChemInform Abstract: Solid Phase Metallurgy Strategy to Sub‐5 nm Au—Pd and Ni—Pd Bimetallic Nanoparticles with Controlled Redox Properties. Issue 11 (18th March 2014) - Tang, Yu; Xu, Shaodan; Dai, Yihu; Yan, Xiaoqing; Li, Renhong; Xiao, Liping; Fan, Jie
Abstract The title bimetallic nanoparticles are prepared by loading Au and Pd, or Ni and Pd nanoparticles into mesoporous silica with extra large pores followed by thermal annealing at 550 °C under H2/Ar atmosphere.